Предмет: Алгебра,
автор: altanwhite
Помогите тотожнисть решить
Приложения:

Ответы
Автор ответа:
1
1. (b²/(a³-ab²)+1/(a+b)=b²/(a*(a²-b²))+1/(a+b)=b²/(a*(a-b)(a+b))+1/(a+b)=
=(b²+a*(a-b))/(a*(a+b)(a-b))=(a²+b²-ab)/(a*(a+b)(a-b)).
2. (a-b)/(a²+ab)-a/(b²+ab)=(a-b)/(a*(a+b))-a/(b*(a+b))=
=((a-b)*b-a*a)/(ab*(a+b))=(ab-b²-a²)/(ab*(a+b))=-(a²+b²-ab)/(ab*(a+b)).
3. (a²+b²-ab)/(a*(a+b)(a-b)):(-(a²+b²-ab)/(ab*(a+b))=-b/(a-b)=b/(b-a).
Evgenia4836:
почему в первом действии + поменялся на -?
Похожие вопросы
Предмет: Английский язык,
автор: isjust335
Предмет: Литература,
автор: ansaganb21
Предмет: Математика,
автор: Аноним
Предмет: Геометрия,
автор: jok32kimmich